The Need Analysis of Participation in an English Immersion Village at Kampung Inggris Pare - Pratiwi, Widya Rizky; Atmowardoyo, Haryanto; Salija, Kisman (Universitas Negeri Makassar, 2020)
The privilege of English as an international lingua franca force many countries to open a wider opportunity for society to learn the language. However, the unbalance between societal needs and the role of English as a foreign language in Indonesia sometimes find the obstacles in the process of learning. This paper reveals the learners’ initial perception of English and analyzes the need for participation in an English immersion program. 24 participants from six English institutions contributed to this qualitative study. The data collected through participant observation and semi-structured interviews for three months in Kampung Inggris Pare, Kediri, East Java, Indonesia. Most of the learners had a negative perception of English before participating in this immersion program that they perceived this language was difficult. This perception is associated with negative experiences during the process of learning English at school. However, their awareness of low self-confidence and poor speaking performance in facing globalization invited them to participate in an English immersion village in Kampung Inggris Pare. This paper concludes that the necessities, the lacks, and students' desire underlie the need analysis of participating in an English immersion program in Kampung Inggris Pare.